Analysis of Speech and Thought Presentation in Children’s Storybook Frozen: A Stylistic Study - Putu Mayra Elke Shafira; Ni Made Diana Erfiani; Yohanes Octovianus L. Awololon (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
Stylistic speech and thought presentation play crucial roles in shaping characters and enriching readers' experiences in children’s storybooks. This study delved into the depiction of speech and thought in the